2013
DOI: 10.1152/jn.00194.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cortical feedback on the spatial properties of relay cells in the lateral geniculate nucleus

Abstract: Feedback connections to early-level sensory neurons have been shown to affect many characteristics of their neural response. Because selectivity for stimulus size is a fundamental property of visual neurons, we examined the summation tuning and discretely mapped receptive field (RF) properties of cells in the lateral geniculate nucleus (LGN) both with and without feedback from visual cortex. Using extracellular recording in halothane-anesthetized cats, we used small luminance probes displaced in Cartesian coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 86 publications
7
60
1
Order By: Relevance
“…The observed reduction in classical receptive field size with enhanced CG feedback is consistent with the finding that pharmacological inactivation of cat visual cortex led to an increase in the size of LGN receptive fields (15). These authors also demonstrated that the strength of surround suppression was reduced when CG feedback was inactivated (15). It is therefore possible that enhanced CG feedback increases the influence of the surround, leading to a reduction in the effective size of the classical receptive field.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The observed reduction in classical receptive field size with enhanced CG feedback is consistent with the finding that pharmacological inactivation of cat visual cortex led to an increase in the size of LGN receptive fields (15). These authors also demonstrated that the strength of surround suppression was reduced when CG feedback was inactivated (15). It is therefore possible that enhanced CG feedback increases the influence of the surround, leading to a reduction in the effective size of the classical receptive field.…”
Section: Discussionsupporting
confidence: 86%
“…Receptive fields and tuning properties of LGN neurons are mainly inherited from the retina and not from CG feedback. However, some prior studies of CG function have argued that feedback could modulate certain properties such as receptive field size (15). We found that LED stimulation of CG feedback significantly reduced the width of the classical receptive field for LGN neurons of both ON and OFF types (Fig.…”
Section: Influence Of Cg Feedback On Lgn Neuronal Receptive Field Sizmentioning
confidence: 52%
See 1 more Smart Citation
“…(described above). To reduce the influence of response variability, the area summation data were fit to a difference of Gaussians equation (Sceniak et al, 2001;Andolina et al, 2013;Alitto and Usrey, 2015a) as follows:…”
Section: Discussionmentioning
confidence: 99%
“…'I'm looking at the kitchen counter'; reviewed in Gilbert and Li, 2013). Experimentally, with cortical feedback intact and visual stimuli employed that exceed the classical center and surround, LGN neurons are more selective in their responses relative to when visual cortex is inactivated (Sillito et al, 1993;Cudeiro and Sillito, 2006;Jones et al, 2012;Andolina et al, 2013;see review, Sillito et al, 2006). Particularly striking are changes in selectivity associated with two sets of gratings drifting in orthogonal directions: one confined to the classic center and surround the other, absent from the center/surround, but occupying the next ~20° .…”
Section: Implementation Of the Principle Of Graceful Degradationmentioning
confidence: 99%